THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND PROFESSIONAL MANAGEMENT THROUGH SUSTAINABLE BUSINESS ON ORGANIZATIONAL PERFORMANCE - Andari, Fika; Sutanto, J.E (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Purpose, The aim is to understand the influence of good corporate governance and professional management through sustainable business on organizational performance. Case study in the family business environment of an Indonesian autobus company. Study design/methodology/approach, the population in this research are PO bus company owners in Indonesia who are members of the Indonesian bus owner community. The total population is 180 companies that are members of the PO bus business community in Indonesia. Analyzing data using the SmartsPLS program, it is Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings, the results of hypothesis testing, both direct and indirect effects, first, are positive and significant; second, positive and significant; the third is negative and not significant; fourth, positive and significant; fifth, positive and significant; sixth, positive and significant; and seventh , positive and significant. Originality/value, it is hoped that the results of this research will increase the amount of literature related to the title of this research and will also be useful for further researchers related to PO bus companies, with a provincial and national level scope. Therefore, the researcher suggests that future researchers use or replace or add other variables that have not been studied.